Identification of Potential Cytokinin Responsive Key Genes in Rice Treated With Trans-Zeatin Through Systems Biology Approach - Mishra, Dwijesh Chandra; Arora, Devender; Budhlakoti, Neeraj; Solanke, Amolkumar U.; Mithra, S. V. Amitha CR; Kumar, Anuj; Pandey, P. S.; Srivastava, Sudhir; Kumar, Sanjeev; Farooqi, M. S.; Lal, S. B.; Rai, Anil; et al. (Frontiers in Genetics, 2022)
Rice is an important staple food grain consumed by most of the population around the world. With climate and environmental changes, rice has undergone tremendous stress state which leads to impact the crop production and productivity. Plant growth hormones are essential component that controls the overall outcome of growth and development of the plant. Cytokinin hormone plays an important role in plant immunity and defense system which is mediated by multi-step two component phosphorelay system that have different roles in various developmental stages and trans-zeatin is an active form of cytokinin that can affect plant growth. Systems biology approach for pathway analysis to trans-zeatin treated rice could provide a deep understanding of different molecules associated with them. In this study, we have used weighted gene co-expression network analysis method to identify the functional modules and hub genes involved in cytokinin pathway. We have identified nine functional modules comprising of different hub genes which contribute to the cytokinin signaling route. Biological significance of these identified hub genes has been tested by applying well proven statistical techniques to establish the association with the experimentally validated QTLs and annotated by DAVID server. Establishment of key genes in different pathways has been confirmed. These results will be useful to design new stress-resistant cultivars which can provide sustainable yield in stress specific conditions.